At the Crossroads of Translation and Cognition: Tracing Decision Making in Translation through Think-Aloud Protocol - Ezginaz Emirkadi (İstanbul Üniversitesi Çeviribilim Dergisi)
Among many definitions, translation can be described as decision making, which involves the concepts of problem solving, strategies, and choices, situating translation as a process which is oriented to study what goes on in the mind of the translators. Then, decision making can be addressed in studies concerning the translator, rather than the product, and can be tackled within the field of translation process research. This is already the case for think-aloud protocols (TAP), studied by many scholars within the framework of decision making. In spite of the criticism it gets, it is obvious that TAP provide rich data on decision making in translation, enhancing a wider perspective on the process-oriented approaches. Based on this perspective, then, TAP can also be studied within the situated and distributed cognition approaches to translation as a valuable research method that has access to the “black box” that will also provide an awareness of the fact that translation decision making and problem solving are not only restricted to texts. In this review, how decision making and translators are studied in translation process research will be reviewed, making some suggestions for future studies.